(untitled) (Asian Business Research, 2017)
This study focuses on a transfer pricing taxation (TPT) action as one of corporate governance issues. TPT is a tool for preventing the manipulation of transfer pricing. We investigate which factors affect corporate valuation, using a sample of Japanese companies to which TPT was unintentionally applied. With this regard, we put emphasis on the role of corporate governance for the preparation against a risk event. In addition, we attempt to determine what kinds of corporate governance structure are most likely to prepare for an unexpected TPT inspection. As a result of our examination, we find that the association of the directors‟ shareholding ratio (DIR) with the cumulative abnormal rate of return (CAR) is statistically significant. We also find that this relation has both a hump and a negative hump, which implies that it is a cubic function. Based on these results, we conclude that a DIR of about 5% is the optimum ratio for a firm facing an emergency situation, and this shows some implications about what kinds of corporate governance structure. Keyword: alignment effect, entrenchment effect, CAR, nonlinear relation, directors‟ shareholding ratio